The Prevalence and Risk Factors of Abnormal Vision Among Preschool Children - Liu D; Zhang L; Shou M; Yu H; Yang Y; Cheng H (Pediatric Health, Medicine and Therapeutics)
Dan Liu, Li Zhang, Mengna Shou, Hong Yu, Yanqing Yang, Hong Cheng Shaoxing Maternity and Child Health Care Hospital, Shaoxing University, Shaoxing, Zhejiang, People’s Republic of ChinaCorrespondence: Dan Liu, Email marcia1981@126.comBackground: The presence of abnormal vision during early childhood has been shown to have a substantial impact on the development of visual, motor, and cognitive functions, potentially resulting in long-term adverse psychosocial outcomes. The objective of this study was to examine the prevalence and associated risk factors of abnormal vision among preschool children aged 4– 6 years in Shaoxing, China.Methods: A cross-sectional study was conducted from March to May 2023 in Shaoxing, involving a sample of 9913 children within the specified age range. Parents were interviewed using a structured questionnaire that gathered information on sociodemographic characteristics and other relevant factors.Results: The study revealed that 14.4% of participants had abnormal vision. Logistic regression analysis indicated that individuals who watched TV for more than 3 hours daily had a 2.206 times higher likelihood of developing abnormal vision (P< 0.05). Additional risk factors for abnormal vision included watching TV at a distance of less than 3 meters, misalignment of eyes and screen while watching TV, early exposure to electronic devices before the age of 2, parents are unaware of the impact of chewing on eye development, and lack of promotion of good eye habits in children (P < 0.05). An association was found between parent’s and children’s refractive error (P < 0.05), with good family lighting and a balanced dietary structure being identified as protective factors against abnormal vision.Conclusion: The study concluded that exposure to electronic products was a significant factor in the development of abnormal vision among children aged 4– 6. Furthermore, family environment and genetic predisposition were also found to influence vision. Regular ocular screenings and early interventions may be effective in preventing abnormal vision.Keywords: risk factors, abnormal vision, preschool children, China